ANTIOXIDANT AND ANALGESIC ACTIVITY OF TOTAL FLAVONOIDS OF FORSSKAOLEA TENACISSIMA.: JPUMHS;2024:14:04,22-31 . http://doi.org/10.46536/jpumhs/2024/14.04.557 - Shamaila Zahid1, Rida Javed2, Susan Kakakhel3, Seher Obaid4, Waqas Zahid5, Abida Yasmin6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Total flavonoids of Forsskaolea tenacissima was screened for possible antioxidant and analgesic activities. It was an attempt to isolate total flavonoids from the aerial parts of plant and subject it for further pharmacological screenings. METHODS: Whole plant of Forsskaolea tenacissima was collected from Institute of basic medical sciences, Khyber medical university and the voucher specimen was sent in to the pharmacology department. Hot plate method, writhing method and tail immersion methods were used to investigate the possible analgesic activity and DPPH was used for the determination of antioxidant activity of Forsskaolea tenacissima while ascorbic acid was used as a reference. RESULTS: Mice were divided into six groups and the lethality was zero percent in animals of first three groups while there was 25 %, 50 % and 100 % lethality in animals of group 4 to group 6 respectively. Total flavonoids of Forsskaolea tenacissima has analgesic activity which is ascertained by the hot plate, writhing, and tail immersion procedures. The antioxidant activity was less than the EC50, or 37.20 percent, at a concentration of 62.5µg/ml. Which gradually increases and it reached to 74.10 % at 1000 µg/ml which shows that the plant has antioxidant activity. CONCLUSION: The study shows that the total flavonoids of Forsskaolea tenacissima has antioxidant activity as well as analgesic activity mediated through Hot plate method, writhing method and tail immersion methods. Crude methanolic extract’s initial phytochemical tests that the plant includes flavonoids, which may be what give it its antioxidant properties.